Investigation of Best Operating Conditions for Treatment of Oily Wastewters with Hollow Fiber Ultrafiltartion Membranes - Abbasi, Mohsen; Sebzari, Mohammad Reza (Journal of Membrane and Separation Technology, 2014)
This paper investigates the optimum operating conditions for treatment of oily wastewaters by application of UF process using the Taguchi method. The following operating conditions have been considered in this investigation: Back Wash time; Trans-membrane pressure (TMP); Flow rate and temperature. The optimum operating conditions of UF were found as follows: Backwash time of 5 s; TMP of 2 bar; Flow rate of 12 L min-1 and temperature of 30 °C. Experimental results presents that the importance level of the percentage contributions of each item is: (1) TMP (98.80 %), (2) back wash time (7.85 %), (3) flow rate (1.11 %), and (4) the feed temperature (0.819 %).